THE INTEGRATION OF BEHAVIORAL ARCHITECTURE CONCEPTS IN HEALTHY HOME DESIGN: A SYSTEMATIC LITERATURE REVIEW - muhammad arsya meiza (Universitas Nusa Cendana, 2026)
The role of architecture today is no longer perceived merely as the creation of physical structures, but as an active instrument that influences the behavior, health, and psychological well-being of its users. This research aims to explore and synthesize existing literature to formulate a new conceptual framework that integrates behavioral architecture concepts with healthy home design principles. The method employed is a Systematic Literature Review (SLR), extracting 17 primary articles from reputable national journals (indexed Sinta 1–4) published within the last five years via the Google Scholar database. Based on descriptive analysis using a literature matrix, the findings indicate that spatial elements such as circulation, lighting, aesthetics, and territoriality deterministically shape behavior patterns, reduce stress levels, and enhance the quality of social interaction. This study concludes that the 'healthy home' design paradigm must evolve from mere physical-structural compliance toward a holistic design-based ecosystem centered on human-centered design. This framework is intended to serve as an essential reference for practitioners in developing adaptive dwellings that comprehensively support the residents' quality of life.